Copyright in the Health Sciences Literature: A Narrative Review - Goben, Abigail; Doubleday, Alison F. (Journal of Copyright in Education & Librarianship, 2018)
Health science educators, researchers, and clinicians are regularly faced with challenges surrounding copyright and fair use. However, little is known about how copyright is addressed in the professional literature. In order to identify themes and gaps, the authors undertook a narrative review of articles published in health sciences literature between 2000-2016. Only 154 articles were identified on the topic, which attempted to address areas of concern for educators, researchers, and clinicians across all health science disciplines. Overarching issues were identified including prevalence of misinformation or misunderstandings, particularly around fair use, and the continued need for authoritative copyright education and definition of best practices.